2019
DOI: 10.1021/acs.jpca.9b01983
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of XCH2CN (X = −Cl, −SH) in Argon Matrices

Abstract: We report infrared spectra and photochemical behavior of the potentially astrochemically significant species, mercaptoacetonitrile (HS-CH 2 C≡N) and, for comparison purposes, chloroacetonitrile (Cl-CH 2 C≡N), both suspended in an argon matrix at 6K. Photolytic formation of the isocyano products HS-CH 2-NC and Cl-CH 2-NC were observed as well as CH 3 NSC and CH 3 SCN (in HS-CH 2 CN photolysis). While no dissociation products were observed for Cl-CH 2-CN, photolysis of HS-CH 2-CN produced compounds necessitating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 105 publications
(189 reference statements)
0
9
0
Order By: Relevance
“…The C 2 H 5 SH sample was purchased from Sigma-Aldrich. The spectrophotometric equipment used here, consisting of a Bruker Vertex 70 FTIR spectrometer with 0.2 cm –1 resolution, a closed-cycle helium refrigerator (DE-202SE, Advanced Research Systems) and associated vacuum system, and vacuum manifold for mixture preparation, have been described previously . Matrices were prepared by starting from a degassed sample and then mixing with Ar (5.0 Multax s.c.) or CO (4.7 Praxair) at a molar ratio of 1:1000 (sample/Ar or CO).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C 2 H 5 SH sample was purchased from Sigma-Aldrich. The spectrophotometric equipment used here, consisting of a Bruker Vertex 70 FTIR spectrometer with 0.2 cm –1 resolution, a closed-cycle helium refrigerator (DE-202SE, Advanced Research Systems) and associated vacuum system, and vacuum manifold for mixture preparation, have been described previously . Matrices were prepared by starting from a degassed sample and then mixing with Ar (5.0 Multax s.c.) or CO (4.7 Praxair) at a molar ratio of 1:1000 (sample/Ar or CO).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The resulting luminescence spectra were recorded by a Mightex CCD spectrometer (HRS series, 300–1070 nm spectral range, 1.7 nm resolution). This method is helpful for the indirect detection of atomic sulfur because several emissions may appear, including: c 1 Σ – → a 1 Δ of SO, B″ 3 Π u → X 3 Σ g of S 2 ; B 3 Σ – u → X 3 Σ – g of S 2 , a 3 B 1 → X 1 A 1 of SO 2 and 3 Σ + → X 1 Σ + of OCS, and a 3 Π → X 1 Σ of carbon monosulfide (CS). We previously used the same method to detect free sulfur produced during the photolysis of the mercaptoacetonitrile (HSCH 2 CN) …”
Section: Experimental Methodsmentioning
confidence: 99%
“…Note that, in the former reaction, iodine atoms bond directly to the carbonyl group only Fig. 7 Cryogenic photolysis of 2-sulfanylethanenitrile results in the formation of structural isomeric products (Zapała et al 2019) When similar experiments were used to investigate the photochemistry between CS 2 and the dihalides Cl 2 , Br 2 , and ClBr in a Ar ice matrix, both syn-and anti-halogenothiocarbonylsulfenyl halides based on X-C(=S)-S-Y backbones were detected (X and Y once again being the constituent atoms of the original dihalide), among other products (Fig. 6; Tobón et al 2007).…”
Section: Laboratory Photochemistry Experimentsmentioning
confidence: 99%
“…Solid phase photochemistry of more complex, exotic molecules may yield significant insights into the chemistry of different functional groups found in the interstellar medium. For instance, Zapała et al (2019) recently examined the photolysis of 2-sulfanylethanenitrile in a Ar matrix at 6 K. A related compound, sulfanylmethanenitrile, has already been detected in the interstellar medium (Halfen et al 2009). Their results showed that, among some photo-dissociation products formed via the loss of -CN and -SH groups, several isocyano compounds were produced as a result of photo-isomerisation processes (Zapała et al 2019; Fig.…”
Section: Laboratory Photochemistry Experimentsmentioning
confidence: 99%
See 1 more Smart Citation